Eksistensi Politik Kader Perempuan pada Pengorganisasian Partai-partai Politik - Mayrudin, Yeby Ma'asan; Nurrohman, Bayu; Astuti, Dewi Sri (International Journal of Demos (IJD), 2022)
This paper aims to examine the issue of the political existence of women cadres in the organizations of political parties. The issue of women's involvement is a crucial issue because of the perpetual shackles of patriarchal culture and the stigmatization of the existence of women. This often leads to unfair practices and the exclusion of women. The research method used is a qualitative descriptive method formulated by Lambert et al with a focus on literature review. The results of this study indicate that the importance of redefining the meaning of political parties that are accommodative to women’s issues (feminism) and the political existence of women from the past until now is considered progressively transformative because it has been proven to mobilize collective awareness actions about the importance of playing a role in efforts to realize gender justice.